Air Transport in Iraq: A Legal Analysis - Ahmed Khalil, Raed; Yaacob, Nurli; Mohamed, Khadijah (IJMR, 2017)
In Iraq, the air transport of persons, goods and luggage, even in the case of domestic carriage, is governed by the provisions of the Warsaw Convention of 1929 and its amendments according to Article 170 of the Iraqi Civil Aviation Act No 148 of 1974 and Article 126 of the Iraqi Transportation Act No 80 of 1983. The Warsaw Convention and its amendments cover the issues pertaining to the liability of air carrier in case of death or bodily injury of a passenger; destruction, loss or damage to checked baggage; and delay of passengers and baggage during the flight. However, these conventions do not cover important aspects of the passengers' rights in air transport sector and contain many vague terms such as accident, bodily injury, embarking, disembarking and delays. This article attempts to provide an overview of the legal framework of air transport in Iraq and the necessity to make amendments to this legal framework in order to ensure the rights of passengers in this sector. For this purpose, the article was prepared with reference to systematic analysis by applying a document analysis method